Decline in left ventricular early systolic function with worsening kidney function in children with chronic kidney disease: Insights from the 4C and HOT-KID Studies - Gu, Haotian; Azukaitis, Karolis; Doyon, Anke; Erdem, Sevcan; Ranchin, Bruno; Harambat, Jerome; Lugani, Francesca; Boguslavskyi, Andrii; Cansick, Janette; Finlay, Eric; Gilbert, Rodney; Kerecuk, Larissa; et al. (Journal of the American Society of Echocardiography, 2024)
Introduction - Adults with childhood-onset chronic kidney disease (CKD) have an increased risk of cardiovascular disease. First-phase ejection fraction (EF1), a novel measure of early systolic function, may be a more sensitive marker of left ventricular dysfunction than other markers in children with CKD. - Objective - To examine whether EF1 is reduced in children with CKD. - Methods - Children from the 4C and HOT-KID studies were stratified according to estimated glomerular filtration rate (eGFR). The EF1 was calculated from the fraction of left ventricular (LV) volume ejected up to the time of peak aortic flow velocity. - Results - The EF1 was measured in children ages 10.9 ± 3.7 (mean ± SD) years, 312 with CKD and 63 healthy controls. The EF1 was lower, while overall ejection fraction was similar, in those with CKD compared with controls and decreased across stages of CKD (29.3% ± 3.7%, 23.5% ± 4.5%, 19.8% ± 4.0%, 18.5% ± 5.1%, and 16.7% ± 6.6% in controls, CKD 1, 2, 3, and ≥ 4, respectively, P < .001). The relationship of EF1 to eGFR persisted after adjustment for relevant confounders (P < .001). The effect size for association of measures of LV structure or function with eGFR (SD change per unit change in eGFR) was greater for EF1 (β = 0.365, P < .001) than for other measures: LV mass index (β = −0.311), relative wall thickness (β = −0.223), E/e’ (β = −0.147), and e’ (β = 0.141) after adjustment for confounders in children with CKD. - Conclusions - Children with CKD exhibit a marked and progressive decline in EF1 with falling eGFR. This suggests that EF1 is a more sensitive marker of LV dysfunction when compared to other structural or functional measures and that early LV systolic function is a key feature in the pathophysiology of cardiac dysfunction in CKD.
Gesehen am 05.11.2024